MT1G activation in dopaminergic neurons identifies chelators and their relationships to cytotoxicity - Zhi-Bin Tong; Srilatha Sakamuru; James Travers; Tuan Xu; Shu Yang; Menghang Xia; Anton Simeonov; Ruili Huang; David Gerhold (SLAS Discovery, 2025)
Although multiple pesticides and solvents are risk factors for Parkinson’s disease [1] and other neurodegenerative diseases, most risk factors remain undiscovered. We previously identified the metallothionein gene MT1G as a biomarker for neurotoxicity induced by all seven neurotoxicants tested in LUHMES dopaminergic neurons. Here we used CRISP/R technology to insert a HiBiT tag into the MT1G gene of the LUHMES cell line. The engineered LUHMES MT1G::HiBiT cell lines were used to develop a quantitative high throughput screening [2] assay in a 3D-suspension culture platform with 1536 well microplates. We validated this qHTS assay by screening the LOPAC (Library of Pharmacologically Active Compounds) collection composed of 1280 compounds plus 88 selected Tox21 chemicals, demonstrating high signal-to-noise and reproducibility. In screening this library, 49 compounds were confirmed to significantly increase MT1G-HiBiT activity, including 35 compounds that exhibited cytotoxicity below 50 μM, and 14 noncytotoxic compounds. Most of these MT1G-HiBiT inducers killed cells at concentrations moderately higher than their MT1G-HiBiT activation potencies (AC50), however 14 showed MT1G-HiBiT AC50 values more than 3-fold lower than cytotoxicity IC50 values, and two showed higher values. Among the 49 MT1G-HiBiT inducers, 45 compounds resembled chelators. To test this apparent association, 27 known chelators were gathered and tested. Of these, 23 were active in the MT1G-HiBiT activity assay, confirming the propensity of chelators to activate MT1G transcription. Screening chemical libraries with this validated assay and characterizing the effects of active chemicals on cultured neurons may enable the identification of neurotoxicants or neurotoxic chemotypes that may cause neurodegenerative diseases.